America’s Middle Schools: Examining Context, Organizational Structures, and Instructional Practices - Ryan Alverson; Mike DiCicco; Shawn A. Faulkner; Chris Cook (Middle Grades Review, 2021)
The education of the young adolescent has consistently posed a challenge to the educational community. While the general belief is this age group (10-15-year-old children) would benefit from a specialized educational approach, historically, both the junior high school model of the early 1900s and the more current middle school concept have struggled to be fully implemented and embraced by the educational community. With almost a decade passing since the last national survey focused on middle grades schools (McEwin & Greene, 2010, 2011), researchers seek to reassess the context, organizational structures, and instructional practices of middle schools in the United States. Over 1,600 responses from principals and teachers to the national survey indicate the status of middle schools is largely unchanged since the McEwin and Greene (2010, 2011) study. Specific recommendations for moving forward are shared.
Keywords: middle school; junior high; adolescent